2014
DOI: 10.1007/s10995-014-1460-9
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Patient Experiences in the Pediatric Patient-Centered Medical Home: A Comparison of Two Instruments

Abstract: The Patient-Centered Medical Home (PCMH) is a model of care that has been promoted as a way to transform a broken primary care system in the US. However, in order to convince more practices to make the transformation and to properly reimburse practices who are PCMHs, valid and reliable data are needed. Data that capture patient experiences in a PCMH is valuable, but which instrument should be used remains unclear. Our study aims to compare the validity and reliability of two national PCMH instruments. Telephon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 17 publications
0
2
0
Order By: Relevance
“…While there is almost no published psychometric testing of the CAHPS, one study reported the reliability of the child-specific scales to be good and the convergent validity to be much higher than the discriminant validity, as expected, yet goodness-of-fit statistics were outside of the acceptable range to claim construct validity of all scales. 13 In this study, our team administered the CAHPS Clinician & Group Expanded 12-Month Child Primary Care Survey with PCMH Items (hereafter referred to as "CAHPS survey") in 2 cross-sectional waves, first in 2011 and again in 2013. There were 6 standard composite scores on this CAHPS survey; of these 6, this study focused on the 2 childspecific composites for "child's growth and development" and "child's health and safety."…”
Section: Patient Experience Surveymentioning
confidence: 99%
“…While there is almost no published psychometric testing of the CAHPS, one study reported the reliability of the child-specific scales to be good and the convergent validity to be much higher than the discriminant validity, as expected, yet goodness-of-fit statistics were outside of the acceptable range to claim construct validity of all scales. 13 In this study, our team administered the CAHPS Clinician & Group Expanded 12-Month Child Primary Care Survey with PCMH Items (hereafter referred to as "CAHPS survey") in 2 cross-sectional waves, first in 2011 and again in 2013. There were 6 standard composite scores on this CAHPS survey; of these 6, this study focused on the 2 childspecific composites for "child's growth and development" and "child's health and safety."…”
Section: Patient Experience Surveymentioning
confidence: 99%
“…A total of 63 reports were included in this review, representing 61 unique interventions 41–103 . Furthermore, we consulted additional publications, which were cited in the eligible reports, for additional details about 23 of the 61 included interventions during our data charting 104–132 …”
Section: Resultsmentioning
confidence: 99%